IT Project Management Practice at PT. Bank BRI Syariah - Suhatman, Zaldy; Firman, Aries F (The Indonesian Journal of Business Administration, 2014)
Abstract— PT. Bank BRISyariah (BRIS)  has three pillars of strategic plans for the bank development, the first pillar is general business affairs to increase commercial performance, linkage, retail and the third party fund. The second pillar boosts business growth in micro business, consumer financing and office channeling optimization. As the foundation there are network, Core banking and IT Application, Human Resource and Culture, Operation, Risk Management. Core banking and IT Application must able to support three pillars of strategic plan, BRISyariah as growing company need Core banking development and IT Application Development conducted by IT Group is a fast, efficient and cost friendly. Currently an application development project carried out by using SDLC (System Development Life Cycle) method as contained in Circular Letter of Bank Indonesia, if only using this method are still many inefficiencies. There are, however, methods of PMI (Project Management Institute) that is based on the PMBOK (Project Management Book of Knowledge), which is the reference for project managers around the world. Then this final project aims to look at the factors of inefficiencies in the development process with the current method and process efficiency Core banking development and IT applications by combining methods of SDLC and PMBOK. These factors were obtained based on the results of interviews with some respondents who are in the IT group itself and also the respondent from another group that is often associated with process development and process development Core banking IT Applications.  Application of PMBOK combined with SDLC best practices so as to produce a solution that can reduce or eliminate inefficiencies. Best practice solutions to be built for 1 year starting with a preparatory phase for 6 months consisting of socialization to users, and then to IT Staff, Training and PMP certification to project manager and implementation Project Management application system. then proceed with the change management program for implementation and monitoring during the next 6 months. Important after the implementation phase is monitoring and feedback to ensure that best practice solution can make the development process core banking and IT applications become more efficient and effective Key words: Project management, Information Technology, SDLC, PMBOK.